(untitled) (Journal of actual problems of jurisprudence, 2016)
In the article the general rules of judicial activity of court are analysed in contention criminal procedure. An accent is done on the changes brought in criminal procedure by a new legislation. Tasks and plenary powers are examined ships following from principle of contentionness. The terms of establishment of equality of rights of parties are analysed in the Kazakhstan criminal trial. A comparative analysis is conducted with a former legislation.